Культурно-мистецька та просвітянська діяльність бібліотеки-читальні в містечку Мацеїв Ковельського повіту Волинського воєводства (1920–1930-ті рр.) - Трофімук-Кирилова, Тетяна; Чибирак, Світлана; Trofimuk-Kyrylova, Tetyana; Chybyrak, Svitlana (My University, 2016)
У статті проаналізовано історію виникнення та функціонування «Просвіти» в 1920–1930-х рр. у містечку Мацеїв Ковельського повіту Волинського воєводства. Охарактеризовано правові засади, на яких ґрунтувалася робота просвітянської бібліотеки-читальні в містечку, а також показано роль місцевої еліти в популяризації української культури. Окремо висвітлено театральну діяльність просвітян.The article deals with the history of origin and functioning the atheneum of Kovel partnership «Prosvita» in Maciejewe during 1920-1930. This study characterizes the legal foundations upon which the work of educational atheneum was based. Besides the role of the local elite in popularization of Ukrainian culture is shown. The musical and theatrical activities of members of different sections of the atheneum are separately highlighted, for example: the organization and staging the performances, concerts, Shevchenko’s academies, children's parties.
Cultural and Art and Educational Activities of Atheneum in Maciejewe of the Kovel District Volyn Province (1920-1930)
Keywords: «Просвіта»; бібліотека-читальня; театральна діяльність; «Prosvita»; library’s reading room; theatrical activity; Maciejewski gmina; Kovel district